2011
DOI: 10.1177/0146167211406507
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and Capitalization Support Are Substantially Similar: Implications for Social Support Theory

Abstract: Social support is typically thought to protect people from bad events, whereas capitalization support augments people’s reactions to good events. Because social support and capitalization support apply to different classes of events, most theory predicts that measures of perceived support and capitalization support should be empirically distinct. We tested a new theory that hypothesizes that the main effects between perceived support and mental health do not reflect stress and coping primarily, but instead ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
(74 reference statements)
4
36
0
Order By: Relevance
“…Behavioral observation studies of established relationships and experimental manipulations with strangers have yielded the same results. Most relevant to the present research, Shorey and Lakey (2011) reported that perceptions of typical capitalization responses were correlated with perceived availability of support for negative events.…”
Section: Support For Positive Events and Successesmentioning
confidence: 70%
“…Behavioral observation studies of established relationships and experimental manipulations with strangers have yielded the same results. Most relevant to the present research, Shorey and Lakey (2011) reported that perceptions of typical capitalization responses were correlated with perceived availability of support for negative events.…”
Section: Support For Positive Events and Successesmentioning
confidence: 70%
“…A supportive response style was negatively correlated with passive and destructive response tendencies. The PRCA has been shown to be valid as evidenced by strong positive associations with observer ratings of responses to capitalization attempts (Gable et al., 2006) and positive correlations with perceived social support (Shorey & Lakey, 2011). As for validity, people who tend to receive supportive responses from their partner following positive event disclosures report greater personal well-being, relationship quality, and relationship longevity (Gable et al., 2004, 2006; Reis et al., 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Social support refers to a network of connections with other human beings that can provide positive assistance, support, guidance, and help for a person (Harvey, 2014;Shorey & Lakey, 2011;Thoits, 2011). As Taylor (2011) pointed out, "social support can also involve simply the perception that such resources are available, should they be needed" (p. 193).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As noted by Colvin, Cullen, and Vander Ven (2002), "organized networks of human relations can assist people in meeting both expressive and instrumental needs, which prevents crime" (p. 24). Social support can also help reduce the chances of mental and physical problems from strains (Shorey & Lakey, 2011). In addition, social support can help workers deal with the problems and strains that they encounter in the workplace (Keinan & Maslach-Pines, 2007;Neveu, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%